Heat Release Rate Markers for the Adelaide Jet in Hot Coflow Flame - Ferrarotti, Marco; Amaduzzi, Ruggero; Bascherini, Davide; Galletti, Chiara; Parente, Alessandro (Frontiers in Mechanical Engineering, 2020)
Favre-Averaged Numerical Simulations of the Adelaide Jet in Hot Coflow burner are carried out to study correlations between the Heat Release Rate and both species mole fractions and net reaction rates. A modified Eddy Dissipation Concept model is employed to implement a detailed kinetic scheme, including also the excited species OH*, conventionally used as Heat Release Rate marker. The effect of oxygen dilution, which, if strong enough, can lead to Moderate or Intense Low-oxygen Dilution (MILD) combustion, is investigated, by analyzing the correlations for two levels of oxygen concentrations. The results suggested the possibility of combining more chemical species to reconstruct an appropriate scalar able to better correlate with the Heat Release Rate (HRR). Indeed, it was found that for the configurations of interest, radicals O, OH, OH* correlate fairly well with the HRR, but even better correlations can be achieved with appropriate products of species mole fractions. This finding is particularly relevant for the MILD region of the flame.